Investigate the Relationship between Corporate Entrepreneurship with Financial Performance in Pakistan: An Empirical Study - Tuba Nafees; Prof. Dr. Muhammad Shafiq; Prof Dr. Khalid Hafeez (Journal of Management Research, 2024)
The main purpose of this research is to look into the link between corporate entrepreneurship and financial performance in Pakistani manufacturing firms. Corporate entrepreneurship is becoming increasingly popular among huge corporations. The idea is employed in major corporations to stimulate innovation or to improve the company’s performance. Existing companies’ new ventures confront numerous obstacles, and data suggests that the majority of them fail. For large corporations, corporate entrepreneurship is very important. This is a quantitative study that used a questionnaire research methodology since it was deemed appropriate for this type of research. The respondents were chosen from the manufacturing sector of the Lahore Chamber of Commerce using simple random sampling. The study’s target population was managers in Pakistan’s manufacturing industry. This study employed a sample size of 307 people from a population of 10,000. The validity and reliability of the research instruments utilised in the study were tested in a pilot study. The Statistical Package for Social Sciences (SPSS) was used to analyse the study’s findings (SPSS version 21). For assessing associations between variables, the researchers utilised the Pearson-Correlation Coefficient and the Multiple Linear Regression Model. The study established that corporate entrepreneurship dimensions (innovation, new business ventures, strategic renewal, pro-activeness, risk-taking, and autonomy) were found to have a statistically significant link with financial performance in the study. Strategic renewal and autonomy were also found to have a high relationship with financial performance in the study. According to the findings, corporate entrepreneurship features such as innovation, new business ventures, risk-taking, strategic renewal, pro-activeness, and autonomy have a favourable impact on manufacturing companies’ financial performance in Pakistan. The report suggests that managers in Pakistan’s manufacturing sector concentrate on corporate entrepreneurship characteristics. You’ll need a goal and a plan if you want your corporate entrepreneurship attempts to succeed. Open to risk, encourage partnerships, create skills and expertise, offer management assistance, allow access to critical resources, maintain a supportive organisational structure, and set realistic performance targets are all characteristics of the most successful entrepreneurial cultures. For the best results, don’t forget to analyse your entrepreneurial environment on a frequent basis.